Effects of a mixed vector-scalar screened coulomb potential for spinless particles - De Castro, Antonio S. (World Scientific Publ Co Pte Ltd, 2006)
The problem of a spinless particle subject to a general mixing of vector and scalar screened Coulomb potentials in a two-dimensional world is analyzed and its bounded solutions are found. Some unusual results, including the existence of a bona fide solitary zero-eigenmode solution, are revealed for the Klein-Gordon equation. The cases of pure vector and scalar potentials, already analyzed in previous works, are obtained as particular cases.
Keywords: Klein-Gordon equation; screened Coulomb potential; vector-scalar potential